Lysis Centrifugation Method for the Direct Identification of Positive Blood Cultures Using MALDI-TOF MS. (4th October 2017) - Al Sidairi, Hilal; BinKhamis, Khalifa; Head, Joline; Davidson, Ross
Abstract: Background: Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) bacterial identification has revolutionized clinical microbiology. Typically, bacteria must be first cultured prior to identification; however, several techniques have emerged that allow the identification of bacteria directly from certain specimen types, including blood cultures. The aim of this study was to compare a direct MALDI-TOF MS identification technique of positive blood cultures with those having at least 4–6 hours of sufficient growth Methods: Only blood cultures flagged overnight as positive by the BD Bactec® were included for study. A one ml aliquot was drawn and immediately processed using a lysis centrifugation technique and analyzed using MALDI-TOF (bioMérieux). Positive blood culture samples were also sub-cultured onto agar plates as per standard laboratory practice, incubated for 4–6 hours and if sufficient growth was present, processed using MALDI-TOF. Cultures with insufficient growth are incubated overnight. Direct identifications were compared with those where sufficient growth was achieved Results: Between June 2015 to February 2016, 300 positive blood cultures were included for study. Of these there were 156 Gram-positive cocci, 112 Gram-negative bacilli, 15 anaerobic organisms, 11 Gram-positive bacilli and 6 yeast. Using a confidence threshold of 99.9%, 69% of all organisms were correctly identified using the direct identification method. The identification of any organism with a confidence threshold <99.9% was not accepted. Approximately 81% of Gram-negative bacilli were correctly identified compared with 64% of Gram-positive cocci 36% of Gram-positive bacilli. Conclusion: The lysis-centrifugation direct identification method is a relatively inexpensive ($1.00) and rapid technique that will allow clinicians to receive the identification of organisms from approximately 70% of bacteremic patients 6 to 24 hours early than waiting for sufficient growth. This should allow clinicians to make better informed empiric antimicrobial choices to manage their patients. Disclosures: All authors: No reported disclosures.